PROSES PENDAFTARAN TANAH LELANG PADA KANTOR PERTANAHAN KABUPATEN SLEMAN - , FEBRIANA KUSUMA WARDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background choice of theme in this final report is that the transition of land rights is not only due to a legal event, but also because of a legal action. Examples of transfer of rights over land because the event is inheritance law, in the absence of any legal act performed transitional land rights will automatically move. While the transfer of rights in land as a legal act such example is the auction. The purpose of internship were to carry out the student can gain real knowledge and can apply the knowledge that has been given in college in the internship. While the benefits are students will be better prepared to enter the real working world later. To register a right to the land , one must have the right to advance. The rights can be obtained through the gain rights for illegal and legal events. Transfer of rights for auction is a legal act performed by the creditor because the debtor can not fulfill its obligations. Basic auction is conducted encumbrance certificate held by the lender as collateral .